Antimicrobial effects of essential oils on oral microbiota biofilms - Aires, Andreia (2021)
Teresa Semedo-Lemsaddek was financially supported by national funds through the FCT—Foundation for Science and Technology, I.P. under the Transitional Standard—DL57/2016/ CP1438/CT0004. Publisher Copyright: © 2020 by the authors. Licensee MDPI, Basel, Switzerland.